Assessing primary care organization and performance: Literature synthesis and proposition of a consolidated framework. Issue 2 (February 2021) - Senn, Nicolas; Breton, Mylaine; Ebert, Sonja T.; Lamoureux-Lamarche, Catherine; Lévesque, Jean-Frédéric
Highlights: Many frameworks describing primary care (PC) organization exist. This study proposes a new consolidated framework based on seven published frameworks. This framework may provide a foundation to support researchers and policy makers. Abstract: Background and objectives: Many frameworks describing primary care (PC) organization exist. This study proposes a consolidated framework based on the synthesis of published frameworks for the assessment of primary care organization and performance. Approach: We conducted a review of the literature to identify relevant existing frameworks that aimed to describe PC organization or/and monitor its activities. First, we extracted all domains from the frameworks and then hierarchically organized them into domains, dimensions and elements. Second, we mapped key domains. Third, we grouped together domains covering the same field to build a consolidated framework. Finally, the consolidated framework was assessed by 10 international experts in PC evaluation using a survey. Results: We retained seven frameworks. The consolidated framework comprises four domains: 1) population needs; 2) organization and structure of PC practices; 3) delivery of PC services and 4) patient and population health outcomes. We added five connecting constructs to the framework in order to link the domains: accessibility, appropriateness, productivity, efficiency, effectiveness, equity and integration. None of the previously published frameworks encompassed all domains, dimensions and elements of the new consolidated framework. Conclusion: We propose a consolidated framework of PC organization based on the synthesis of seven published frameworks. This unitary framework may provide a foundation for comparative assessment across various contexts to support researchers and policy makers.